Frost depth prediction for seasonal freezing area in Eastern Turkey - Orakoğlu, Müge Elif; Liu, Jiankun; Tutumluer, Erol (My University, 2016)
This paper presents the results of an investigation relative to the prediction of frost depths of seasonal freezing area in eastern Turkey. The Stefan equation and a modified Berggren equation are compared and utilized, and the computed results are compared with actual observed data. Also, the different harmful effects of freezing–thawing on highways in eastern Turkey are elucidated, supplemented with case studies. Based on this, the coldest areas are defined and a freezing depth contour map with the region's transportation network is produced. Some recommendations for the design and maintenance of subgrades in cold regions are provided.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Frost-related problems; Frost heave; Subgrade; Cold regions in Turkey